ISNAR Annual Report 2001 - International Service for National Agricultural Research (International Service for National Agricultural Research, 2002)
During 2001, ISNAR poised itself for an environment where international investors in development are awakening to the failure of their past strategies, and where national governments are reconsidering their tools for alleviating poverty. This Annual Report highlights seven examples of the concentrated effort ISNAR is making to create institutional innovation through mobilizing talents in the South.